Supermassive black hole mass measurements for NGC 1300 and NGC 2748 based on HST emission-line gas kinematics - Atkinson, J; Collett, J; Marconi, A; Axon, D; Alonso-Herrero, A; Batcheldor, D; Binney, J; Capetti, A; Carollo, C; Dressel, L; Ford, H; Gerssen, J; et al. (2005)
We present Space Telescope Imaging Spectrograph emission-line spectra of the central regions of the spiral galaxies NGC 1300 and NGC 2748. From the derived kinematics of the nuclear gas we have found evidence for central supermassive black holes in both galaxies. The estimated mass of the black hole in NGC 1300 is 6.6 (+6.3, -3.2) x 10^7 solar masses and in NGC 2748 is 4.4 (+3.5, -3.6) x 10^7 solar masses (both at the 95% confidence level). These two black hole mass estimates contribute to the poorly sampled low-mass end of the nuclear black hole mass spectrum.